Urban middle-school students' attitudes toward a defined science - Zacharia, Zacharias; Calabrese Barton, Angela (Science education (Salem, Mass.), 2004)
Recent studies have shown that urban students and students of color have exceptionally negative attitudes toward school science and their futures in that field as compared with white students and nonurban students. In this paper we summarize research findings on students' attitudes toward science. We note that most of the studies of students' attitudes toward science that have been conducted so far have measured students' attitudes against the backdrop of a generalized science. Thus, we develop a detailed argument for why science needs to be more clearly defined in attitude instruments. We report on our development of this instrument as well as our initial findings.